Zika Virus Induced Mortality and Microcephaly in Chicken Embryos - Goodfellow, Forrest T; Tesla, Blanka; Simchick, Gregory; Zhao, Qun; Hodge, Thomas; Brindley, Melinda A; Stice, Steven L (Stem cells and development, 2016)
The explosive spread of the Zika virus (ZIKV) through South and Central America has been linked to an increase in congenital birth defects, specifically microcephaly. Representative rodent models for investigating infections include direct central nervous system (CNS) injections late in pregnancy and transplacental transmission in immunodeficient mice. Microcephaly in humans may be the result of infection occurring early in pregnancy, therefore recapitulating that the human course of ZIKV infection should include normal embryo exposed to ZIKV during the first trimester. In ovo development of the chicken embryo closely mirrors human fetal neurodevelopment and, as a comparative model, could provide key insights into both temporal and pathophysiological effects of ZIKV. Chick embryos were directly infected early and throughout incubation with ZIKV isolated from a Mexican mosquito in January 2016. High doses of virus caused embryonic lethality. In a subset of lower dosed embryos, replicating ZIKV was present in various organs, including the CNS, throughout development. Surviving ZIKV-infected embryos presented a microcephaly-like phenotype. Chick embryos were longitudinally monitored by magnetic resonance imaging that documented CNS structural malformations, including enlarged ventricles (30% increase) and stunted cortical growth (decreased telencephalon by 18%, brain stem by 32%, and total brain volume by 18%), on both embryonic day 15 (E15) and E20 of development. ZIKV-induced microcephaly was observed with inoculations of as few as 2-20 viral particles. The chick embryo model presented ZIKV embryonic lethal effects and progressive CNS damage similar to microcephaly.